Topical Issues of Administration of Migration Processes on Space of the CSTO in Modern Conditions - Alexey M. Voronov (Евразийская интеграция: экономика, право, политика, 2019)
The purpose given works is improvement of legal administration of migration processes on space of the CSTO in modern conditions. On the basis of scientific methods of knowledge, the author analyzes the current state of the studied perspective, topical issues of legal regulation of migration processes as in global world scale, and applicable the territory which is under jurisdiction of the CSTO are studied. The author the reasons reveal and conditions of emergence of undesirable migrations when under the guise of refugees fighters get on the adjacent territory for commission of acts of terrorism come to light. Summarizing the author it is advisable to initiate consideration of a question of legislative restriction of undesirable migrations not only in theRussian Federation, but also in the CSTO State Parties as borders “are absolutely transparent” here.